Keyakinan teori konspirasi sebagai mediator hubungan antara identitas agama dengan sikap terhadap radikalisme kekerasan - Muhammad Syafiq; Nurchayati Nurchayati; Hermien Laksmiwati; Ira Darmawanti (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2023)
This study was aimed at examining the Muslim students’ attitude towards radicalization which reflects their approval or rejection of radicalization by involving the factor of Religious Identity as the dependent variable and Belief in Conspiracy Theory as the mediator. The sample was Muslim students in public and private universities in East Java. The sample was selected using snowball technique by relying on the networks of friendship owned by the researchers to be forwarded in sequence to the researchers’ friends’ networks. The data was collected online through a google form containing 3 (three) Likert model questionnaires, namely the attitude scale towards radicalization, belief in conspiracy theories, and religious identity. A total of 651 respondents filled out this research questionnaire. Data were analyzed using Macro PROCESS 3.0 from Hayes with IBM's SPSS 25.0 for windows program. The results showed that there was a significant positive correlation between religious identity and attitudes towards radicalization, as well as between belief in conspiracy theories and attitudes towards radicalization. This study also proves that belief in conspiracy theories can partially mediate the relationship between religious identity and attitudes towards radicalization. The results of this study can be taken into consideration in making policies to promote the prevention of the radicalization process among college students.